FAKTOR-FAKTOR YANG MEMENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH DI KOTA YOGYAKARTA - Listia Ningsih; Amir Hidayatulloh (Jurnal Riset Akuntansi Politala, 2022)
The aim of this study was to analyze the factors that influence the use of accounting information in Micro, Small and Medium Enterprises (MSMEs) in Yogyakarta City. The population of this study is MSMEs throughout the Special Region of Yogyakarta. The sample of this research is MSMEs located in the city of Yogyakarta. The sampling technique used purposive sampling, with the criteria of SMEs that have used and utilized accounting information. The data were collected by distributing questionnaires directly to respondents who met the criteria. The data analysis technique used multiple linear regression analysis. This study obtained the results that the use of accounting information influenced by the education of the owner/manager. However, the usage of accounting information is not influenced by accounting training factors, business scale, or business age